2019
DOI: 10.7567/1347-4065/ab4b6d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on effects of electron thermal energy on sensitization process of chemically amplified electron beam resists—contribution to resist heating effect in electron beam mask writing

Abstract: The elevation of resist temperature during exposure to electron beam (EB) deforms the patterns of chemically amplified resists. The resist heating effect is a significant problem in mask production using a high-current EB mask writer. However, its mechanism is still unknown. In this study, the effects of electron thermal energy on the sensitization process of chemically amplified EB resists were investigated using simulation on the basis of their sensitization mechanism. The decomposition yield of sensitizers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The acid generator concentration used for the acid yield measurement in this study was 0.114 molecule nm −3 . In accordance with the reported procedure, 24) the heating effect for 0.114 molecule nm −3 was calculated to be 0.038% K −1 . The heating effect measured experimentally in the acid yield measurement was at least 0.14% K −1 for the PHS film.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…The acid generator concentration used for the acid yield measurement in this study was 0.114 molecule nm −3 . In accordance with the reported procedure, 24) the heating effect for 0.114 molecule nm −3 was calculated to be 0.038% K −1 . The heating effect measured experimentally in the acid yield measurement was at least 0.14% K −1 for the PHS film.…”
Section: Resultssupporting
confidence: 60%
“…Using the Monte Carlo simulation for the sensitization mechanism of chemically amplified EB resists, we investigated the effect of the energy of thermalized electrons on the radical cation yield. 24) The increase in electron thermal energy reduced the effect of the Coulomb attraction produced by the radical cations in the geminate ion recombination process. This led to an increase in the reaction probability of thermalized electrons with acid generator molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8) However, a high acceleration voltage results in a long-range proximity effect, heating and charging effects, and time-consuming exposure process. [9][10][11] An E-Beam Mask Writer with a low acceleration voltage can overcome the earlier mentioned disadvantages; however, a low acceleration voltage results in a relatively low short-range resolution. 12,13) Although studies have reported that EUV masks exhibit strong electron scattering in the multilayer and low local patterning quality at high acceleration voltages, the mechanism of electron scattering within each layer at low acceleration voltages (i.e.…”
Section: Introductionmentioning
confidence: 99%